Analysis of the Impact of Hydraulic System Fluid Quality on the Efficient Operation of Universal-Type Tractors - Meliyev Xudoyor Oblayorovich; Tursunov Dilshod Mukhamadbekovich (Genius Journals, 2022)
The article discusses the analysis of the share of faults associated with the contamination of fluids in the hydraulic system of Universal-type tractors and the impact of fluid quality on the coefficient of technical readiness.
Keywords: Universal tractor; hydraulic system; operational reliability; failure